Quality Of Duck Eggs At Different Soaking Times In Noni Leaf Extract Stored For 15 Days - Sri Sukaryani; Engkus Ainul Yakin; Hardika Eka Rhamadanu (Bantara Journal of Animal Science, 2021)
Duck eggs are one type of protein source food that is much favored by the people of Indonesia.  However, currently there are not many ways of preservation to maintain the quality of duck eggs in storage.  With preservation by immersion with noni leaf extract, it can be an alternative in maintaining the quality of duck eggs in storage for 15 days.  This is because noni leaves contain elements of chemical compounds such as amino acids, phenolic compounds, ursulic acid, alkaloids, phenols, and glycosides which are antimicrobial, antibacterial and anti-inflammatory.  This study aims to determine the effect of soaking duck eggs in noni leaf extract on the interior quality of duck eggs.  This study used a completely randomized design (CRD) with a concentration of 45% noni leaf extract with immersion time of 0, 12, 24, 36 and 48 hours with 3 replications.  To determine whether there is a difference in treatment using Duncan Multiple Range Test (DMRT) at the level of = 0.05.  The research variables are Albumen Insex, Yolk Index and Haugh Index.  Data were analyzed by SPSS.  The results of the study concluded that soaking duck eggs with noni leaf extract for 12-48 hours with an extract concentration of 45% had no significant effect on egg quality in this case the yolk index, albumen index and Haugh index.